Financial Management Practices in Islamic Donation-based Crowdfunding (DCF) Platforms in Malaysia - Muhammad Iqmal Hisham Kamaruddin; Nurul Aini Muhamed; Wan Nur Fazni Wan Mohamad Nazarie; Rafisah Mat Radzi; Aimi Fadzirul Kamarubahrin (Springer Nature, 2024)
Indexed by WOS